2019
DOI: 10.1063/1.5125037
|View full text |Cite
|
Sign up to set email alerts
|

Thermal boundary resistance predictions with non-equilibrium Green's function and molecular dynamics simulations

Abstract: The non-equilibrium Green's function (NEGF) method with Büttiker probe scattering self-energies is assessed by comparing its predictions for the thermal boundary resistance with molecular dynamics (MD) simulations. For simplicity, the interface of Si/heavy-Si is considered, where heavy-Si differs from Si only in the mass value. With Büttiker probe scattering parameters tuned against MD in homogeneous Si, the NEGF-predicted thermal boundary resistance quantitatively agrees with MD for wide mass ratios. Artifici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Copyright 2020 American Chemical Society. transmission functions from AMM, DMM, AGF, or phonon wave-packet method [71,257,[267][268][269][270][271][272][273]. Within the framework of MD methods, nonequilibrium MD (NEMD) [274][275][276] and interface conductance modal analysis [115,143,[277][278][279][280][281][282][283] are usually applied to predict h BD .…”
Section: Enhancement Of Thermal Transport Across Power Electronics Interfaces (Shi and Graham)mentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2020 American Chemical Society. transmission functions from AMM, DMM, AGF, or phonon wave-packet method [71,257,[267][268][269][270][271][272][273]. Within the framework of MD methods, nonequilibrium MD (NEMD) [274][275][276] and interface conductance modal analysis [115,143,[277][278][279][280][281][282][283] are usually applied to predict h BD .…”
Section: Enhancement Of Thermal Transport Across Power Electronics Interfaces (Shi and Graham)mentioning
confidence: 99%
“…However, it is very difficult to include anharmonicity in Landauer approach, and the consideration of detailed interface structure or interface bonding strength in AMM or DMM is very hard to implement. Recently, there are several studies of considering anharmonicity in AGF [270,279], but there are still some limitations like high computational costs and inaccuracy from estimated scattering rate at interfaces. At interfaces between two crystalline materials, because of the growth limitation, the crystalline quality of one or both of the materials near the interface is usually not very good or the interfacial bonding is not very strong from different growing methods, like evaporation [262], CVD [115,280], and atomic layer deposition [281,284].…”
Section: Enhancement Of Thermal Transport Across Power Electronics Interfaces (Shi and Graham)mentioning
confidence: 99%
“…(27). Here we keep the convention of using local energy density to characterize the local temperature in nonequilibrium transport as currently done in the heat transport community [21,[67][68][69].…”
Section: Macroscopic Variable Calculationmentioning
confidence: 99%
“…Very few works [43,44,[62][63][64][65][66] directly take into account the anharmonic phonon-phonon scattering, yet often consider few-atom systems like the atomic chain or junction [43,44,62,63], and single-unit-cell interface [66]. An indirect treatment of incoherent phonon scattering was also proposed by the Büttiker probe approach [67][68][69] inspired by its counterpart in electron NEGF, yet it relies on fitting the anharmonic scattering rates with empirical expressions. The challenge in NEGF modeling of anharmonic heat transport comes from not only the difficulty in numerical implementation, but also the less established theoretical formalism.…”
Section: Introductionmentioning
confidence: 99%
“…Classical lattice dynamical theory is quite powerful to make prediction; we mainly adopt this perspective to elucidate this problem. The relatively rigorous approaches such as Molecule dynamics simulation and non-equilibrium Green's function method require accurate atomic-level interface boundary information plus huge computational expenses, which are not included in this review but can be found in other works [27,[82][83][84][85].…”
Section: Thermal Boundary Conductancementioning
confidence: 99%